Implementation of the Subscription Parking Policy on Ahmad Yani Street by the Medan City Transportation Department - Rambe, Fika Nadya; Siregar, Nina Siti Salmaniah; Sinaga, Rudi Salam (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze the implementation of the Regulation of the Minister of Education and Culture (Permendikbud) No. 1 of 2021 concerning Online New Student Admissions (PPDB) at the secondary education level at SMAN 1 Sunggal. The Permendikbud is expected to increase efficiency, transparency, and equal access in accepting new students. However, in its implementation, there are various challenges that must be faced, such as limited technological infrastructure, public understanding of the online system, and inequality of internet access in several regions. This study uses a qualitative approach with a case study method that focuses on SMAN 1 Sunggal. Data were collected through interviews with the school, direct observation, and documentation related to the implementation of online PPDB. Data analysis was carried out using descriptive analysis techniques to identify various obstacles and solutions that can be applied in the implementation process of online PPDB. The results of the study show that although the online PPDB system at SMAN 1 Sunggal has been running relatively well, there are several challenges, such as inequality of internet access in certain areas and lack of public understanding regarding online registration procedures. However, this system has succeeded in reducing fraudulent practices and simplifying the administration process for accepting new students. Therefore, it is necessary to improve technological facilities and training for prospective students and parents to support the successful implementation of the online PPDB system in the future. This research is expected to contribute to the development of educational policies and improve understanding of the application of technology in the educational process in Indonesia.